(untitled) (Práxis Educativa, 2022)
This article presents a reflection on experiences that took place between schools and Quilombola communities in the state of Bahia, Brazil, based on Law no. 10.639/2003, that refers to the articulation between the educational processes that took place in schools and communities, especially with regard to the field of curriculum. The theoretical framework adopted is from a decolonial perspective and the methodology used was of a qualitative nature, using semi- structured interviews with teachers. It was concluded that, when it comes to education proposals committed to cognitive/social justice and life in its diversity, the participation and representation of subjects should not be reduced to mere formality, as it is necessary to create real conditions for the effective participation of communities in relation to schools, whether in the elaboration or the implementation and evaluation of specific curricular policies in their territories. Keywords: Quilombola education. School-community relationship. Law no. 10.639/2003.